Analisis Penerimaan dan Penggunaan Website Training Center di Universitas X Menggunakan Technology Acceptance Model (TAM) - Muhammad Galih Ramaputra; Hendri Purnomo; M. Yhogha Ismail Ibn Ibrahim (Jurnal Komputasi, 2025)
In the digital era, the use of information technology in education is crucial to enhance the effectiveness of learning and training. University X has developed a Training Center website as a supporting platform for academic and professional activities for students and educators. This study analyzes the acceptance and use of the website using the Technology Acceptance Model (TAM), with the main variables being Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Use (ATU), Behavioral Intention to Use (BI), and Actual System Usage (ASU). The research method employed is a quantitative survey through the distribution of questionnaires to students, lecturers, and educational staff. The results show that PU scored 75.2%, PEOU 8.69%, ATU 75.37%, and BI 77.5%, indicating that users have a positive perception of the benefits and intention to use the website, although there are still challenges regarding ease of use. To improve the website's effectiveness, it is recommended to optimize features, integrate with the Learning Management System (LMS), and enhance outreach and training for users. The results of this study are expected to serve as a basis for further development to increase the acceptance and usage of the Training Center website at University X.